PENGARUH POLISAKARIDA KRESTIN DARI EKSTRAK JAMUR Coriolus versicolor TERHADAP PROFIL PROTEIN TERSTIKULER DAN KADAR TESTOSTERON Mus musculus - Astuti Wahyuningsih, Sri Puji; Gibson, Virid; Hayati, Alfiah (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2016)
The purpose of this research was to determine the effect of polysaccharide krestin (PSK) on the testicular protein profiles and testosterone levels of Mus musculus with variety of dosages. This research used a completely randomized design. It were devide into four treatment group i.e. control group, PSK treatment at a dose of Â 15, 30, 60 mg/kgBW. Each group had six replications. Testicular proteins were isolated by flushing technique and analized by SDS-PAGE. Testosterone levels were analized using ELISA technique at wavelength 450 nm. Protein bands analysis showed that there were no diversification between four treatments. Molecular weight of protein bands were 87, 63, 57, 35, and 30 kDa. The results of research showed that the testosterone levels at dosage 60 mg/kgBW had significanly different with control, PSK treatment of 15 and 30 mg/kgBW. PSK treatment of Â 60 mg/kgBW had lowest level at dosage, i.e. 25946.8 Ïg/mL. It can be concluded that giving variety of dosages of polysaccharide krestin did not affect to testicular protein profiles but giving effect to testosterone levels of Mus musculus.